Analisis Profitabilitas Perusahaan Ayam Petelur PT Suni Tama Perdana Desa Kertosari Kecamatan Singorojo Kabupaten Kendal - Fitri Dian Perwitasari; W. Roessali; T. Ekowati (Universitas Wahid Hasyim, 2009)
This research was aimed to find how many profitability with sales volume, active and investment make in ratio-ratio profitability for 3 years. This research was conducted from april month 2005 in layer farm “PT Suni Tama Perdana” Kertosari vilage, Singorojo District Kendal Regency. The research used study case method and samples were taken by purposive sampling. The data obtained were analysed ratio-ratio profitability was “profit margin”, “return on assets” (ROA), “return on equity”(ROE) dan “return on invesment” (ROI). The results showed that analysis profitability layer farm in “PT Suni Tama Perdana” have good work because profit enough and can be back investment to investor. Key word: layer chicken, cost and ratio-ratio profitability.